Genotoxic impact of BPA and analogs (BPE, BPZ, and BADGE) on Mytilus galloprovincialis: insights from biomarker analysis - Beyza Nalbantlar; Özlem Çakal Arslan (Academia Biology)
The number of analogs being produced and substituted for bisphenol A (BPA), which belongs to the class of endocrine disruptors, is increasing day by day. The genotoxic effects of analogs such as bisphenol E (BPE), bisphenol Z (BPZ), and bisphenol A diglycidyl ether (BADGE)—containing almost the entire alphabet—were investigated on the Mytilus galloprovincialis species exposed to increasing concentrations. When comparing their effects on gills, it was observed that BADGE and BPA had similar impacts, with the micronucleus (MN) frequency determined as BPA (32‰) > BADGE (26.5‰) > BPE = BPZ (24.6‰), respectively. Similarly, concerning hemolymph, the MN frequency was determined as BPA (31.2‰) > BPZ (28.6‰) > BPE (26.1‰) > BADGE (21.6‰), respectively. Nuclear bud formation in cells exposed to BPE is believed to affect the MN frequency. Comparing their impact on hepatopancreatic cells, the MN frequency was observed to be BPA (27.7‰) > BADGE (23.4‰) > BPZ (22.1‰) > BPE (21‰), respectively. All chemicals were noted to increase the MN frequency in hemolymph, gill, and hepatopancreas cells concerning the control and duration of exposure. Overall, all chemicals significantly increased MN frequency in hemolymph, gill, and hepatopancreas cells compared to controls, with variations based on the chemical and exposure duration. This research underscores the need for continued investigation into the genotoxic potential of BPA analogs for the safety and sustainability of aquatic ecosystems.